Analisis Pengaruh Total Moisture terhadap Kehilangan Massa Batubara akibat Swabakar di Stockpile 1, Tambang Air Laya, PT Bukit Asam (Persero) Tbk - Denny Ramadi Halim; Maulana Yusuf; Restu Juniah (Dinasti Research, 2026)
Spontaneous combustion can decrease the efficiency of the coal supply chain. One parameter affecting spontaneous combustion is total moisture. This research aims to improve coal handling efficiency and prevent losses caused by spontaneous combustion. This study used a quantitative descriptive method with a case study approach. The data used are proximate test data and spontaneous combustion simulation results from coal samples of 4,200 kcal/kg, 4,900 kcal/kg, 5,300 kcal/kg, and 7,100 kcal/kg. The analysis was conducted by comparing the relationship of total moisture to spontaneous combustion susceptibility and coal mass reduction, and providing technical recommendations for stockpile management. The results indicate a significant positive correlation between total moisture and the susceptibility level of coal to spontaneous combustion. Coal with high TM content (calorific value of 4,200 kcal/kg with an average TM of 36.64%) recorded the highest temperature of 725°C. Meanwhile, 7,100 kcal/kg coal with an average TM of 6.8% reached the lowest temperature of 547.6°C. The relationship between total moisture and coal mass loss is directly proportional, meaning higher total moisture results in greater coal mass lost to spontaneous combustion. Coal of 4,200 kcal/kg with a high TM of 36.64% experienced a mass reduction of 90.12%. In contrast, 7,100 kcal/kg coal with a lower TM of 6.80% proved more stable and experienced a mass loss of 71.82%. Technical recommendations to minimize spontaneous combustion include modifying stockpile geometry, layered compaction, storage segmentation, periodic stockpile clearing, and preparing proper base and drainage systems.